Enhancing Some Physical Properties of Cosmetic Face Powders - Karar Abdali (Journal of Global Pharma Technology, 2018)
In present paper, calculation of refractive index values at different temperature ranges of some cosmetics face powders before and after adding polyethylene glycol (PEG) polymer have been measured. The temperatures range values were (30, 35, 65) °C. The results show that, the index of refraction values decreased with increasing of temperatures in that thermal range, that is lead to decrease the transparency of medium and make it more burnish. By mixing method a blend solution have been prepared and tested on face powders and taking a best result of absorbing UV-rays all colloidal diagnosed by (FTIR) spectrums.Keywords: Cosmetics, Face Powders, PEG and Refractive Index.